Hashemite Kingdom of Jordan - Poverty Update : Main Report - World Bank (World Bank, 2012)
This report is a joint product of the Jordanian Department of Statistics (DOS) and the World Bank. The report has four goals: 1) update the official Jordanian poverty line based on the 2006 Household Income and Expenditure Survey (HIES) using the methodology previously applied for the poverty assessment in 2002; 2) describe recent poverty trends; 3) understand the reasons for the discrepancy between the results of formal statistical analysis and popular perceptions of poverty trends; and 4) provide preliminary information about the distributional impacts of fuel subsidies and measures to compensate for fuel subsidy elimination. Using 2006 as the base year, the Jordanian poverty line was JD 46.3 per person per month. In 2006, 13 percent of the population was below the poverty line. The highest rate of poverty was observed in Mafraq governorate. Although Amman has the lowest poverty rate of all governorates, it is home to the largest number of poor individuals due to the concentration of population in Amman. Several sub-districts, including Rwashed, Wadi Araba and Aghwar Janoobiyah have very high rates of poverty. Disturbingly, income would have fallen for most Jordanians if not for growth in transfer income. The growth in transfer income was primarily due to transfers made to compensate for the April 2006 fuel price increases and gifts to government employees announced by the King on holidays. Income before transfers is comprised mainly of property/rental and labor income. Property/rental income fell between 2002 and 2006, apparently reflecting the dis-saving trend also observed at the macro level. Labor income was stagnant for most Jordanians, although the wealthiest quintile saw significant gains.